1982
DOI: 10.1038/hdy.1982.25
|View full text |Cite
|
Sign up to set email alerts
|

A search for peas (Pisum sativum L.) showing strain specificity for symbiotic Rhizobium leguminosarum

Abstract: A wide variety of primitive pea types and other genetic stocks was tested under gnotobiotic conditions for nodulation and nitrogen fixation with each of two strains of Rhizobium leguminosarum. A strain of Turkish origin (3624) formed active nodules on all 375 pea lines tested, while 24 peas from Afghanistan, 1 from Israel and 1 from Turkey were totally or partially resistant to nodulation by the other strain (2550), which was of European origin. Tests with other Rhizobium strains established that the plasmid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Previously investigations under field conditions (Hobbs and Mahon 1982;Rengel 2002;Young et al 1982) have shown that some Rhizobium isolates are more efficient when inoculated on some genotypes than on others. Huntington et al (1986) concluded from their greenhouse study that the host/ endophyte combination forms a relatively ineffective symbiotic association being primarily inherent in the host plant rather than the endophyte or the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previously investigations under field conditions (Hobbs and Mahon 1982;Rengel 2002;Young et al 1982) have shown that some Rhizobium isolates are more efficient when inoculated on some genotypes than on others. Huntington et al (1986) concluded from their greenhouse study that the host/ endophyte combination forms a relatively ineffective symbiotic association being primarily inherent in the host plant rather than the endophyte or the environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Turkish Rhizobium strain TOM can nodulate the Afghanistan pea and also commercial European cultivars. This extended host range is a property linked to the symbiotic plasmid p RL5JI present in TOM (YOUNG et al, 1982).…”
Section: Introductionmentioning
confidence: 98%
“…They were obtained by screening with a commercial inoculant mixture, and not tested further for strain specificity. More recently, a smaller screen of 375 pea varieties was conducted at the John Innes Institute (Young et a!., 1982a(Young et a!., , 1982b. Twenty-six lines, nearly all from Afghanistan, were resistant to a strain of R. leguminosarum from England, 383 but were nodulated by TOM.…”
Section: Introductionmentioning
confidence: 99%